Infrared Spectral Investigations of Adsorption and Oxidation of N,N-Dimethylaniline by Sepiolite, Loughlinite and Diatomite - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Springer, Dordrecht, 1987)
The adsorption behaviour of sepiolite,loughlinite (Na-sepiolite) and diatomite for N,N-dimethylaniline (DMA) and its catalytically formed oxidation products are studied using IR spectroscopy. It is found that sepiolite and loughlinite adsorb DMA and then react with it more easily than diatomite. The adsorption capacity sequence of DMA for the minerals studied is sepioliteandgt;loughliniteandgt;diatomite.
Keywords: Oxidation Product; Differential Thermal Analysis; Vibrational Band; Methyl Violet; Magnesium Silicate